2020
DOI: 10.1111/risa.13499
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Influencing the Risky Cycling Behaviors of Young Cyclists Aged 15–24 Years: A Questionnaire‐Based Study in China

Abstract: Road traffic crashes are the leading cause of death for young people, among whom cyclists account for a higher percentage of injuries and deaths than any other road users. This study aimed to examine the factor structure of the Young Cyclist Behavior Questionnaire (YCBQ) and investigate the relationships among demographic characteristics, cycling use‐related variables, perceived risk, perceived cycling skills, and risky cycling behaviors among young people. A sample of 448 cyclists (mean age of 20.37 years) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 70 publications
5
18
0
1
Order By: Relevance
“…It is widely known that traffic casualties constitute a challenging barrier to the sustainability of road safety [6]. As previously reported, people tend to choose transport modes that they perceive as safer [7].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is widely known that traffic casualties constitute a challenging barrier to the sustainability of road safety [6]. As previously reported, people tend to choose transport modes that they perceive as safer [7].…”
Section: Introductionmentioning
confidence: 81%
“…For instance, better cyclist-driver awareness and more interaction between car drivers and cyclists are among the recognized strategies that should improve bicycle safety [3]. Also, recent evidence has shown that one of the most important factors affecting the safety of road users is their own behavior; however, low awareness among road users seems to be a challenging issue to face [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…e government can internalize it by taxation and fees increase such as raising fuel prices and levies fuel taxes to raise the travel cost of private cars. Congestion fees will be levied on vehicles driving on congested roads according to their vehicle types to reduce the frequency of private cars [21,22]. Furthermore, uplifting of parking fee level in downtown area could reduce urban traffic pressure.…”
Section: Make the External Cost Of Private Car Travel An Internalmentioning
confidence: 99%
“…e male riders would not tolerate to wait the next green-light; therefore, they are prone to infringe the traffic regulation. And males are more likely to engage in risky behaviours (i.e., traffic light violation) [53].…”
Section: Analysis Of E-bikers' Characteristicsmentioning
confidence: 99%